Directing the wind: Techno-economic feasibility of green ammonia for farmers and community economic viability - Ofori-Bah, Catherine Obiribea; Amanor-Boadu, Vincent (Frontiers in Environmental Science, 2023)
There has been increasing interest in low-carbon technologies to reduce climate change impacts. However, careful assessments of their implications for the vibrancy of local economies are rare. This paper employs techno-economic analysis to assess the technical and economic feasibility of investment in one such technology: local green ammonia production and its contribution to the economic viability of the local economy. The analysis considers price projection and debt financing options, and alternative energy-to-ammonia technologies. The approach is broadly applicable and is illustrated here using a case study in which 248,188 MT of traditional ammonia are replaced with local wind energy-produced ammonia for farmers in Southwest Kansas, United States. Economic feasibility is defined as the ability to accrue enough discounted cash flow at the end of the turbines’ 25-year lifespan to enable their replacement. The alternative technologies are the traditional Haber-Bosch and the emerging solid oxide electrolysis cell (SOEC). The total plant capital cost amounted to 781.72 million while the plant operating costs were set at 100/MT with the energy supplied by the project’s energy system. The results show how economic feasibility sensitivity to technology and financing options are evaluated and communicated to scientists, policymakers, and farmers. The 6.5 MWh/MT wind energy-to-ammonia SOEC technology presented the best economic results under all price projections. The community’s investment yielded the highest return when debt was used to finance 50% of the capital investment. Returns exceeded the average annual S&P return of about 7% from 1957 to 2021. The work shows how consideration of technology efficiencies and creative financing strategies can contribute to the economic welfare of farmers and their communities even as they contributed to reducing crop production’s carbon footprint.